The Process of Goods Shipment at PT. XYZ Logistics - Tuasikal, Husein (ASIAN PUBLISHER, 2022)
This study discusses the Goods Delivery Process at PT. XYZ Logistics Bekasi. The research method uses observation and library methods. Based on the results of observations or observations that researchers conducted on the goods delivery process at PT. XYZ Logistics Bekasi, researchers found obstacles including shortages in goods sent, damage to the car engine so that delivery was delayed and customers were not served on time, and the solution that researchers propose to overcome obstacles in the problem of goods delivery is the need for delivery vehicle facilities that are suitable for use and adding operational vehicles for goods delivery so that there is no delay in goods delivery, the engine is checked before the truck carries out the process of loading goods so that the process in the goods delivery activity can run well, cooperation and accuracy are needed from warehouse employees in checking orders when loading goods so that there is no shortage or excess of goods that cause the outlet that ordered to experience losses because they have to reorder the goods.